Statistical production of Bc mesons in heavy-ion collisions at the LHC energy - Shouxing Zhao; Min He (Physics Letters B)
The recombination production of Bc mesons in heavy-ion collisions at the LHC energy is facilitated by the abundant and highly thermalized charm (c) quarks transported in the deconfined medium created. We study the production of Bc mesons via c and bottom (b) quark recombination in a statistical fashion by placing Bc in the position of a member of the family of open b hadrons, which allows us to make quantitative predictions for the modifications of the production fraction (fc) of Bc mesons and its relative production to B mesons in sNN=5.02TeV Pb-Pb collisions with respect to proton-proton (pp) collisions at the same energy. The statistical production yield of Bc mesons is converted into the transverse momentum (pT) distribution with the shape computed from resonance recombination using the c- and b-quark phase space distributions that have been simulated via Langevin diffusion and constrained by open c- and b-hadron observables. Supplemented with the component fragmented from b-quark spectrum that dominates at high pT, the total pT spectrum of Bc mesons is obtained and converted into the pT dependent nuclear modification factor (RAA). Both fc and the integrated RAA exhibit a ∼5-fold enhancement in central Pb-Pb collisions relative to the pp reference. Comparison with data measured by the CMS experiment shows decent agreement within theoretical and experimental uncertainties.